2006
DOI: 10.1007/s00415-006-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

The Rivermead Post Concussion Symptoms Questionnaire

Abstract: The results support the notion of post-concussion symptoms as a collection of associated but at least partially separable cognitive, emotional and somatic symptoms, although questions persist regarding symptom specificity. The use of the RPQ is discussed, and classification bands for use in clinical practice are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
215
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(233 citation statements)
references
References 78 publications
17
215
0
1
Order By: Relevance
“…Previous studies have demonstrated that post-concussive symptoms can be broadly categorized into physical, emotional, and cognitive clusters, with a high degree of overlap between them, [19][20][21][22] but neither the incidence of these symptoms nor their relative burden throughout the recovery period have been well described in children. 23,24 Here we show that although the majority of children initially present to care after ARTICLE PEDIATRICS Volume 133, Number 6, June 2014a concussion with symptoms of headache, dizziness, and fatigue, new symptoms often develop during the recovery course, particularly those that have a substantial emotional component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that post-concussive symptoms can be broadly categorized into physical, emotional, and cognitive clusters, with a high degree of overlap between them, [19][20][21][22] but neither the incidence of these symptoms nor their relative burden throughout the recovery period have been well described in children. 23,24 Here we show that although the majority of children initially present to care after ARTICLE PEDIATRICS Volume 133, Number 6, June 2014a concussion with symptoms of headache, dizziness, and fatigue, new symptoms often develop during the recovery course, particularly those that have a substantial emotional component.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite being characterized as somatic symptoms, both sleep issues and fatigue may have a significant emotional component, so careful attention should be paid to coincident emotional symptoms in children who have these complaints. 21 The emotional symptoms of concussion (frustration, depression, irritability, and restlessness) were not commonly reported on presentation, but did develop in large numbers of patients during follow-up and were among the symptoms that lasted the longest. An exception to this was depression, which developed in only 8.6% of patients who did not report it initially.…”
Section: Discussionmentioning
confidence: 99%
“…The number and severity of symptoms were collected using the Rivermead Post-Concussion symptoms Questionnaire (RPQ; [60][61][62]), as in previous studies [11,14,21,39,40,53,63]. PCS was diagnosed if participants reported that three (or more) of the symptom categories listed in the ICD-10 criteria were more of a problem after the head injury.…”
Section: Diagnosismentioning
confidence: 99%
“…The RPCSQ 37-39 is a 16-item self-report of cognitive, emotional, and somatic complaints that are commonly reported after mTBI. Factor analyses have elicited a three-factor solution comprising cognitive, somatic, and emotional problems, 39 although variations have been reported. 40 The participants were asked to rate the severity of each symptom (currently compared with pre-injury levels) from 0 -''not experienced at all'' to 4 -''severe problem.''…”
Section: Emotional and Post-concussion Measuresmentioning
confidence: 99%